Promise and unrealized potential: 10 years of the American Medical Association classifying obesity as a disease - Schumacher, Leah M.; Ard, Jamy; Sarwer, David B. (Frontiers in Public Health, 2023)
Introduction. In June 2013, the American Medical Association (AMA), one of the most influential healthcare organizations in the United States, voted to recognize obesity as a disease. Many who supported this change believed that recognition by AMA of obesity as a disease would serve as a tipping point that would increase access to care, accelerate training and research on the prevention and treatment of obesity, and reduce weight stigma. On the 10-year anniversary of this vote, this perspective piece outlines key advances made, as well as unrealized potential, in improving the obesity public health landscape since the AMA’s classification of obesity as a disease. Methods. We draw on the empirical literature, as well as our experiences as clinical psychologists, a physician, and public health researchers specializing in obesity, to provide an overview of major advances and continued challenges in improving access to obesity treatment, accelerating prevention and training, and reducing weight stigma. We also outline important next steps to advance these goals. Results. While several notable advancements have occurred, significant work remains to create equitable access to evidence-based treatments, bring research and training on obesity on par with its prevalence, and reduce the pervasiveness and harm of weight stigma. Conclusions. The past decade has witnessed some advances with respect to access to care and attention, yet there is unrealized potential that awaits attention. Truly conceptualizing and treating obesity as a chronic disease requires a major paradigm shift.